Obstacles encountered in the practice of planning classes in school Physical Education (Research, Society and Development, 2021)
The present article is a bibliographical research that aimed to reflect on the obstacles found in the planning of classes in school Physical Education. In line with the theoretical framework, it was possible to make some considerations on the subject. In this sense, we observe that, in addition to the lack of materials and adequate infrastructure, the scarcity of studies dealing with the organization of content and the planning of classes in physical education are presented as one of the main obstacles to the pedagogical practice of teachers. In this way, critical pedagogical approaches and guiding documents appear as important proposals for the organization of teaching work. Thus, it is necessary to have a greater debate around studies that can subsidize the pedagogical practice, proposing discussions that contemplate ways to organize and plan the contents of the classes in a systematic and in-depth way. We believe that the discussion on this theme is important so that the Physical Education teacher can base their practice on theoretical knowledge and, consequently, organize the pedagogical work in a critical and reflective way.